The design, detailing, fabrication and execution of architecturally exposed structural steel - Cox, Lindsay (Kansas State University, 2021)
Architecturally exposed structural steel, AESS, is a unique member designation used in contract documents to describe steel members designed according to stringent provisions as to be completely exposed in close proximity to the human eye after the structure is completed, rather than concealed from view. These members are often used to convey architectural art or expression, and have a distinctive beauty that attracts the eye. The requirements for AESS members are much more stringent than those for typical structural steel members, and therefore is more controversial as to whether it is worth the extra attention it requires. The purpose of this report is to examine the design, detailing, fabrication and execution of architecturally exposed structural steel. This is done by examining what contributes to each of these stages from design to field erection. Much of this report is based on guides and sample specification by various sources, including the Structural Engineers Association of Colorado (SEAC), Rocky Mountain Steel Construction Association (RMSCA), and the AISC 303-10 Code of Standard Practice for Steel Buildings and Bridges (American Institute of Steel Construction Committee on the Code of Standard Practice, 2010) in addition to other sources. The conglomeration and in-depth review of this information provides the Structural Engineer, Architect, Fabricator and Owner an enhanced understanding and knowledge of AESS, as to make better decisions throughout its use.
Keywords: Architecture; Exposed; Structure; Steel